2019
DOI: 10.1108/jamr-02-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Power distribution reforms

Abstract: Purpose Distribution and retail supply of electricity is the most important cog in the power sector value chain. Despite several reforms, most of the Discoms are facing huge financial losses and resorting to a tariff hike which may not be a viable solution. The purpose of this paper is to analyze a case study of Tata Power Delhi Distribution Ltd (Tata Power-DDL) which inoculated itself against the financial ills, and demonstrates how a utility can nurture itself and manage the key stakeholder expectation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…At the same time, a sustained supply of clean and inexpensive RE sources is essential to ensure that development does not create environmental issues (Elavarasan et al, 2020). Prior research (Sinha et al, 2020) indicated that public knowledge of RE for sustainable development is a very important enabler.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a sustained supply of clean and inexpensive RE sources is essential to ensure that development does not create environmental issues (Elavarasan et al, 2020). Prior research (Sinha et al, 2020) indicated that public knowledge of RE for sustainable development is a very important enabler.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…, 2020). Prior research (Sinha et al. , 2020) indicated that public knowledge of RE for sustainable development is a very important enabler.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Ghana and China dominated the reviewed CSF PPP papers. 2 The review reflected scarcity in power-focused PPP CSF research [50].…”
Section: Geography Sectors and Yearly Outputsmentioning
confidence: 99%
“…6. Limited focus on external factors: Another potential roadblock is the limited focus of the BSC model on external factors, such as the competitive environment or external stakeholder expectations (Sinha et al, 2019). If the BSC does not adequately capture these external factors, it may not provide a complete picture of the organization's effectiveness.…”
Section: Potential Roadblocks In Applying the Bsc In Different Areasmentioning
confidence: 99%